REALIZATIONS OF MODALITY IN TEACHER-TO-TEACHER TALK OF FORCED ONLINE LEARNING - Citra . Laoli; Rahmad . Husein; Anna Riana Suryanti Tambunan (LINGUISTIK TERAPAN, 2022)
The objective of this study was to describe the ways the modality was realized in teacher-to-teacher talk of forced online learning. The data of this study were sentences expressing modality uttered by teachers while they were talking about forced online learning. Participant observation technique was performed to collect the data. Based on the data analysis conducted it was found that modality was realized through modal operators (47%), modal adjuncts (27%), interpersonal metaphors (16%), and predicator constituents (10%). The use of modal operators which was mostly found in realizing the modality indicates that the teachers tend to talk and think about states of affairs that are not present in the current situation and may never occur in the natural world. Moreover, there are some combinations of the realizations realized, namely: modal adjuncts and interpersonal metaphors; modal operators and predicator constituents; modal operators and modal adjuncts; interpersonal metaphors and predicator constituents; modal operators and interpersonal metaphors; modal operators, modal adjuncts, and interpersonal metaphors; and modal operators, interpersonal metaphors, and predicator constituents. It shows that teachers use some ways to assert or deny and to prescribe or proscribe when they express their judgments on forced online learning especially in informal situations.